Cosmopolitanism and Race in Percy Grainger’s American “Delius Campaign” - Kirby, Sarah (Current Musicology, 2017)
“Cosmopolitanism and Race in Percy Grainger’s American ‘Delius Campaign’” analyzes Grainger’s early-twentieth-century campaign to promote the works of Frederick Delius in the United States, exposing the campaign’s underpinnings in Grainger’s racist, nativist, and eugenicist ideologies and projects. Kirby exposes a peculiar construction of cosmopolitanism at the root of Grainger’s modes of presenting Delius to US audiences, arguing that by downplaying his European national roots, Delius and his music could be deployed as a “blank canvas” upon which Grainger could superimpose his own “developing racist ideologies.”